2010
DOI: 10.1128/jvi.01779-09
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor Gamma by Human Cytomegalovirus for De Novo Replication Impairs Migration and Invasiveness of Cytotrophoblasts from Early Placentas

Abstract: Human cytomegalovirus (HCMV) contributes to pathogenic processes in immunosuppressed individuals, in fetuses, and in neonates. In the present report, by using reporter gene activation assays and confocal microscopy in the presence of a specific antagonist, we show for the first time that HCMV infection induces peroxisome proliferator-activated receptor gamma (PPAR␥) transcriptional activity in infected cells. We demonstrate that the PPAR␥ antagonist dramatically impairs virus production and that the major imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 28 publications
4
59
0
1
Order By: Relevance
“…The use of rosiglitazone in these studies has been shown to inhibit the trophoblastic invasion process 28 and, in particular, to inhibit extravillous cytotrophoblasts invasion and impair early human trophoblast migration. 29 In contrast, PPAR-␥ antagonists were shown to promote extravillous cytotrophoblast cell invasion. 30 However, results from other studies are more consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rosiglitazone in these studies has been shown to inhibit the trophoblastic invasion process 28 and, in particular, to inhibit extravillous cytotrophoblasts invasion and impair early human trophoblast migration. 29 In contrast, PPAR-␥ antagonists were shown to promote extravillous cytotrophoblast cell invasion. 30 However, results from other studies are more consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…40 Activation of PPAR-␥ by human cytomegalovirus also impaired early human trophoblast migration and invasiveness in the EVCT. 41 In recent studies, both Nadra et al 42 and Schaiff et al 43 demonstrated adverse placental development after rosiglitazone administration to healthy pregnant mice, including disorganization of placental layers, altered placental microvasculature, decreased placental expression of angiogenic factors, and thinning of the spongiotrophoblast layer and dilated labyrinthine blood spaces. In both studies, rosiglitazone was administrated during the early stages of gestation and at considerably higher concentrations (30 to 100 mg/kg per day) then that used in the present study (5 mg/kg per day).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the screen does not rule out a role for nuclear receptors that do not meet the cut off. However, PPARγ, which is already known for its positive role during HCMV infection (17), was classified as a hit in the screen, suggesting our methodology was robust and may identify other host factors that play a role during viral replication.…”
Section: Significancementioning
confidence: 99%
“…Cortisol, the glucocorticoid receptor ligand, enhanced virus production in human embryonic kidney cells (16). Most recently, a PPAR response element was described within the MIEP, and a PPARγ antagonist reduced viral protein expression, lipid droplet formation, and virus production (17).…”
mentioning
confidence: 99%